Differential recruitment of DNA Ligase I and III to DNA repair sites - Mortusewicz, Oliver (Oxford University Press, 2006)
DNA ligation is an essential step in DNA replication, repair and recombination. Mammalian cells contain three DNA Ligases that are not interchangeable although they use the same catalytic reaction mechanism. To compare the recruitment of the three eukaryotic DNA Ligases to repair sites in vivo we introduced DNA lesions in human cells by laser microirradiation. Time lapse microscopy of fluorescently tagged proteins showed that DNA Ligase III accumulated at microirradiated sites before DNA Ligase I, whereas we could detect only a faint accumulation of DNA Ligase IV. Recruitment of DNA Ligase I and III to repair sites was cell cycle independent. Mutational analysis and binding studies revealed that DNA Ligase I was recruited to DNA repair sites by interaction with PCNA while DNA Ligase III was recruited via its BRCT domain mediated interaction with XRCC1. Selective recruitment of specialized DNA Ligases may have evolved to accommodate the particular requirements of different repair pathways and may thus enhance efficiency of DNA repair.